PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PKn DI KELAS V - corba, nabella inktau; abidin, zainal; zuraida, zuraida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis study aims to determine how much influence the use of cooperative learning model numbered head together (NHT) on student learning outcomes in PKn learning. This research is a type of quantitative research with experimental research methods, and a quasy experimental design research design. The population in this study amounted to 84 people with a sample size of 32 people, sampling data was carried out by purposive sampling technique. The instruments used were objective tests with multiple choice forms. The results showed that t count> t table is 2.146> 2.04 with α = 0.05 which means Ha is accepted. The average posttest results in the experimental class 81,31 and the control class 75.81. So that Ha is accepted, namely the influence of the use of cooperative learning model numbered head together (NHT) on student learning outcomes in PKn learning. Keywords: Cooperative Model NHT Type, Learning Outcomes, PKn